CURRENT TUBERCULOSIS A IN HIV-INFECTED PATIENTS - Kholiev Bakhodir Oltibayevich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Summary: Tuberculosis is widespread in all regions of the world. According to WHO, in 2016, 476,774 people with tuberculosis had a positive HIV status, which accounted for 7.5% of all reported cases. In 2016, more than 374,000 people living with HIV died from tuberculosis worldwide (WHO, 2017). In recent years, the In the Russian Federation, there is a steady increase in the incidence of tuberculosis in patients with HIV infection. According to the Federal Tuberculosis Monitoring Center, the number of people living with HIV infection has doubled. The article provides an overview of the epidemic indicators of tuberculosis and HIV infection in Russia. Problems of diagnosis of tuberculosis in combination withcoinfection, as well as new laboratory and immunological methods used today in the world and domestic practice to determine tuberculosis infection.